Yield potential of Five Soybean Varieties (Glycine max L) on Acid Dry Land - M. Reza Tanjung; Boy Riza Juanda; Dolly Sojuangan Siregar (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to determine the yield potential of 5 high-yielding soybean varieties cultivated in acid dry land and provide a reference for farmers about superior varieties that are able to produce optimally in acid dry land. This study used a non-factorial randomized block design using 5 superior varieties of soybean seeds, namely Dega 1, Detap 1, Grobogan, Devon 1 and Dena 1. The parameters observed in this study included: plant height, flowering age, number of productive branches. , age of harvest, number of pods per plant, weight of seeds per plant, weight of 100 seeds, and average yield potential. The results showed that each variety has a different response to the environment so that the growth and potential yields obtained are also different. In this study V2 (Detap 1) had the highest production per hectare compared to the other 4 varieties. Yield potential and adaptability are quite good in acid dry land indicated by V2 (Detap 1) indicator of potential yield and adaptability based on the productivity level of the variety.